Child Labor in Africa : Issues and Challenges - Andvig, Jens; Canagarajah, Sudharshan; Kielland, Anne (World Bank, Washington, DC, 2012)
How serious is the issue of child labor in Sub-Saharan Africa? Many African experts consider it to be no problem, while others believe it to be more serious than anywhere else in the world. A cursory glance at the statistics supports either view. ILO data indicate that more than 40 percent of African children work--almost twice as many as in Asia. On the other hand, household surveys suggest that over 95 percent of child labor takes place in and around private households. African society places a high value on children working at home or the family farm. This is not seen as "harmful" or as a welfare issue--a view opposed by many Western countries. This article explores the normative and factual basis for the different perceptions of child labor in Africa, and provides grounds effective social protection policies. Both welfare economic research and findings of sociological and anthropological studies have been reviewed.